A cross-sectional study: exploring the relationship between commuting time and subjective wellbeing in the UAE - Razzak, Hira Abdul; ElShamy, Amin; Harbi, Alya; AlKarbi, Mubarkah; Al Shaali, Lubna; Salama, Rasha; Alosi, Ahmed; Madi, Haifa H. N. (Frontiers in Built Environment, 2023)
Background: Commuting has become an integral part of modern life, impacting individuals’ daily routines and overall wellbeing. The duration of commuting has been recognized as important determinants of subjective wellbeing, with potential implications for public health. Aim: To examine the association between commuting time and subjective wellbeing across the seven emirates of the UAE. Methods: A cross-sectional survey was conducted on adults aged 18 years and above, encompassing both officially employed and self-employed individuals in the UAE. The sample of 5,476 participants was randomly selected from the population across the seven Emirates. To assess subjective wellbeing, the WHO-5 instrument, available in 31 languages and known for its ease of completion, scoring, and interpretation, was employed. Both Arabic and English versions of the tool were provided to the participants. Logistic regression analysis was conducted to investigate the relationship between commuting time and wellbeing, while controlling for individual, social, economic, and environmental factors. The adjusted odds ratios (aORs) were calculated to determine the association with poor wellbeing. Results: The commuting time was associated with a higher odds ratio (OR) of experiencing poor subjective wellbeing. This association remained consistent even after accounting for individual, social, economic, and environmental factors in the analysis models. Among employees with commuting times greater than 60 min, the adjusted OR of poor subjective wellbeing was 2.24 (95% CI, 1.82–2.77) times higher compared to individuals with less than 15 min of commuting time. Similarly, for employees with commuting times between 31 and 60 min, the adjusted OR of poor subjective wellbeing was 1.7 (95% CI, 1.39–2.09) times higher, while for those with commuting times between 15 and 30 min, the adjusted OR was 1.26 (95% CI, 1.04–1.53) times higher, both compared to individuals with less than 15 min of commuting time. Conclusion: The findings of this study indicate that commuting time plays a crucial role in determining the subjective wellbeing of employees in the UAE. Specifically, employees with longer commuting times tend to report lower levels of subjective wellbeing. This suggests a potential opportunity to implement policies aimed at reducing commuting durations, which could ultimately enhance the wellbeing of the employed workforce. Such measures have the potential to positively impact the mental wellbeing of employees in the United Arab Emirates.